A SYSTEMATIC REVIEW OF THE CHANGING PARADIGM OF SHIFTING TENDENCIES IN ONLINE BUYING - Balaji N. P.; Rajini T V (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The advent of the internet has significantly transformed consumer behavior, leading to a paradigm shift in online buying tendencies. This systematic review aims to synthesize the existing literature on the evolution of online purchasing patterns, identifying key trends, factors influencing these changes, and the implications for businesses and consumers. The review highlights the transition from traditional to digital shopping, the role of technology, consumer trust and security concerns, the impact of social media, and future directions in e-commerce.